The Effect of ESG Disclosure on Financial Performance: Moderating Role of Firm Size and Leverage - Rinny Meidiyustiani; Indah Rahayu Lestari (Journal of Economic Education and Entrepreneurship Studies, 2026)
Environmental, social, and governance (ESG) disclosure has become an important mechanism for companies to communicate sustainability commitments and reduce information asymmetry in capital markets. This study examines the effect of ESG disclosure on the financial performance of consumer non-cyclicals companies listed on the Indonesia Stock Exchange, with firm size and leverage initially proposed as moderating variables. Using a quantitative explanatory design, this study employed secondary data obtained from annual reports, sustainability reports, financial statements, and Refinitiv LSEG data over a five-year observation period. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. Financial performance was initially measured using PBV, ROA, and ROE, while firm size was measured by the natural logarithm of total assets and leverage by the debt ratio. The measurement model results showed that ROA and debt did not meet the outer loading criteria and were therefore removed from the final model. The findings reveal that ESG disclosure has a positive and significant effect on financial performance. Firm size also has a positive and significant effect on ESG disclosure but a negative and significant effect on financial performance. However, firm size does not moderate the relationship between ESG disclosure and financial performance. These findings support stakeholder theory and signaling theory by showing that ESG disclosure can function as a value-relevant signal for investors. The study contributes to ESG literature in emerging markets by demonstrating that ESG disclosure directly supports financial performance, although its effect is not contingent on firm size.